KORELASI ANTARA INDEKS MASSA TUBUH (IMT) DENGAN KADAR HB REMAJA DI SMP SATU ATAP DESA SUKA MAJU KECAMATAN MESTONG MUARO JAMBI - Imelda Imelda; Pauline Kusmaryati; Netty Herawati (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
Height and weight can provide an overview of a person's nutrition. Nutritional problems in adolescents can occur because of the continuation of nutritional problems at the age of children, namely iron deficiency, excess and underweight. The human body needs iron for the synthesis of the protein that carries oxygen, namely hemoglobin. Anemia occurs when the production of hemoglobin is so reduced that its levels in the blood decrease. Anemia is still a common nutritional/public health problem associated with the risk of morbidity and mortality, especially in adolescents. Anemia due to iron deficiency affects more than 2 billion people in the world. Data from Riskesdas in 2013 showed that the prevalence of anemia in Indonesia was 21.7% with patients with anemia aged 5-14 years at 26.4% and 18.4% in patients aged 15-24 years. This study aims to determine the correlation between BMI and HB levels in adolescent girls. The research location was conducted at One Roof Middle School, Mestong District, Muaro Jambi Regency from August to December 2018. This research is an analytical study with a cross sectional design. The population in this study were all young women from grade 1 to grade 3 of One Roof Junior High School. A sample of 40 adolescents was taken using the purposive sampling technique. Data analysis was carried out univariate and bivariate with Spearman correlation test. The results of the study showed that the median age of adolescents at One Roof Junior High School, Mestong District 14 (12-17), averaged Hb 14 + 1.64 gr/dl. Average BMI 18.61+2.37. There is a significant correlation between BMI and Hb Levels in One Roof Junior High School Adolescents, Mestong Muaro Jambi District. Expected to be able to cooperate with related parties in the promotion of adolescent health, especially the health of adolescent girls.